1988
DOI: 10.1159/000234673
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a Novel Hydroquinone Inhibitor of Leukotriene Synthesis (U-66,858) in the Rhesus Monkey <i>Ascaris</i> Reactor

Abstract: The IgE-mediated hypersensitivity to Ascaris antigen in reactor rhesus primates was used to assess the pharmacologic profile of U-66,858 (1-acetoxy-2-n-butyl-4-methoxy-naphthalene). When the compound was given by the oral route, it showed dose-related inhibition of resistance (RL) and compliance (Cdyn) changes. When the compound was given by the aerosol route, it showed dose independent inhibition. In 15 animals, aerosols (52 ± 32 to 53 ± 10% for RL, p = 0.05 and 45 ± 19 to 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Many rhesus monkeys possess a natural IgE antibody against the nematode parasite, and their marked broncho constriction is elicited by inhalation of protein extracted from Ascaris suum, which has a cross-reactivity to monkey nematode [1][2][3][4], Models of allergic asthma in naturally sensitized or experimentally infected monkeys have been utilized to determine the effects of various antiallergic or 5-lipoxygcnase-inhibitorv agents, which include ETYA [5], BW-755c [6], U-60257 [7], U-66858 [4], DSCG [3,8,9], PRD-92-Ea [3], ncdocromil sodium [8,9] and L651392 [10]. The results showed that leukotrienes (LTs) play an impor tant role in the pathogenesis of monkey asthma models, as do those in human asthmatic disease, in which LTs are im portant chemical mediators [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Many rhesus monkeys possess a natural IgE antibody against the nematode parasite, and their marked broncho constriction is elicited by inhalation of protein extracted from Ascaris suum, which has a cross-reactivity to monkey nematode [1][2][3][4], Models of allergic asthma in naturally sensitized or experimentally infected monkeys have been utilized to determine the effects of various antiallergic or 5-lipoxygcnase-inhibitorv agents, which include ETYA [5], BW-755c [6], U-60257 [7], U-66858 [4], DSCG [3,8,9], PRD-92-Ea [3], ncdocromil sodium [8,9] and L651392 [10]. The results showed that leukotrienes (LTs) play an impor tant role in the pathogenesis of monkey asthma models, as do those in human asthmatic disease, in which LTs are im portant chemical mediators [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the development of novel therapeutic agents such as the 5‐lipoxygenase inhibitors, which reduce the formation of both LTB 4 and the sulphidopeptides LTC 4 , LTD 4 and LTE 4 . These compounds have proved effective in animal models of human allergic airway disease, inhibiting antigen‐induced bronchoconstriction in a range of experimental animals (McFarlane et al ., 1987; Piechuta et al ., 1987; Johnson & Stout, 1988; Payne et al ., 1988; Abraham et al ., 1992). Moreover, those drugs such as Zileuton, MK‐0591 and Bay X1005, which have reached the stage of clinical trial evaluation in patients with moderately severe asthma, improve airflow and reduce the need for inhaled steroids (Chapman et al ., 1994; Lichey et al ., 1995; Virchow et al ., 1995; Israel et al ., 1996).…”
Section: Discussionmentioning
confidence: 99%
“…AA-861 [-7]. The compound 1-acetoxy-2-n-butyl-4-methoxynaphthalene (U-66,858) is a semiquinone [8] in which conversion, by deacetylation, occurs after contact with blood. The purpose of these experiments was to monitor the conversion of U-66,858 to its deacetylated metabolite U-68,244, and by relating this to the relative activities of the two compounds in vitro, determine whether U-66,858 could behave as a precursor to an active metabolite.…”
Section: Introductionmentioning
confidence: 99%